Characterization of Papillary Thyroid Microcarcinomas Using Sonographic Features in Malignant Papillary Thyroid Cancer. Issue 21 (May 2015) - Gu, Wei-jun; Yan, Hui-xian; Luo, Yu-kun; Wang, Fu-lin; Yang, Guo-qing; Guo, Qing-hua; Jin, Nian; Zang, Li; Chen, Kang; Du, Jin; Wang, Xian-ling; Yang, Li-juan; et al.
<x xml:space="preserve">Abstract</x> Abstract The diagnosis of malignant thyroid nodules is still a clinical challenge. This study aimed to determine the ultrasonographic characteristics of papillary thyroid carcinoma. The ultrasonographic and pathological data of 2453 thyroid nodules in a cohort of 1895 Chinese patients who underwent thyroidectomy from January 2010 to December 2012 were retrospectively reviewed. Anteroposterior and transversal (AP/TR) diameters ≥1, solid structure, infiltrative margins, hypoechoic appearance, and microcalcifications were more common in malignant nodules than in benign nodules (P < 0.01). These ultrasonographic features were independent risk factors of malignancy (P < 0.01) as determined by logistic regression analysis. Based on multivariate analysis, these characteristics were also present in large nodules (diameter >10 mm). However, in small nodules (diameter ⩽10 mm), only AP/TR ≥1 and infiltrative margins were independent risk factors of malignancy (P < 0.01). Ultrasonography is of high diagnostic value for malignant thyroid nodules and may help to improve the differential diagnosis. Small and large nodules have distinct ultrasonographic features.